The development of mathematical competence and the use of assessment instruments - Núñez Cárdenas, Jhoscelyn (2023)
In this article, it is the input of the work whose purpose is to establish the level of development of mathematical skills through the use of evaluation instruments in sixth grade students of primary education of a private IE in the district of San Miguel de la city ​​of Lima in the year 2022, for which sixty students have been submitted to which they are evaluated in pretest and posttest; of which thirty students have been subjected to an intervention where the main tools were the evaluation instruments; the pretest and posttest were a checklist in which the evidence of the development of competences was collected when students develop different problems of intra and extra mathematical context; the research was of an experimental, longitudinal type with a quasi-experimental design with a quantitative approach; after statistical treatment; where it is established that the characteristics of the control group and the experimental group, which are similar at the beginning after the experiment, show relevant differences; likewise, the experimental group shows a significant development before and after the experiment; This development is significant showing the efficiency and effectiveness of the experiment.